Inhibitory effects of Jasminum grandiflorum L. essential oil on lipopolysaccharide-induced microglia activation-integrated characteristic analysis of volatile compounds, network pharmacology, and BV-2 cell - Lu, Jingya; Zeng, Xiaoyan; Feng, Yanping; Li, Siyi; Wang, Yun; Liu, Youlin; Chen, Feilong; Guan, Zhenfeng; Chen, Tiantian; Wei, Fenghuan (Frontiers in Pharmacology, 2023)
Neuroinflammation is being considered as prominent role in the pathogenesis of Alzheimer’s disease (AD). Microglia are the resident macrophages of the central nervous system, modulating microglia activation is a promising strategy to prevent AD. Essential oil of Jasminum grandiflorum L. flowers is commonly used in folk for the relief of mental pressure and disorders, analyzing the volatile compound profiles and evaluating the inhibitory effects of Jasminum grandiflorum L. essential oil (JGEO) on excessive activation of microglia is valuable for its application. This study aims to explore the potential active compounds in JGEO for treating AD by inhibiting microglia activation integrated network pharmacology, molecular docking and the microglia model. A headspace solid-phase microextraction combined with gas chromatography–mass spectrometry procedure was used to analyze the volatile characteristics of the compounds in Jasminum grandiflorum L. flowers at 50°C, 70°C ,90°C and 100°C for 50 min, respectively. A network pharmacological analysis and molecular docking were used to predict the key compounds, key targets and the binding energies based on the detected compounds in JGEO. In the lipopolysaccharides (LPS)-induced BV-2 cell model, the cells were treated by 100 ng/mL LPS and JGEOs at 7.5, 15.0 and 30 μg/mL, then the morphological changes, the production of nitric oxide (NO) and reactive oxygen species (ROS), the expressions of tumor necrosis factor-α (TNF-α), interleukin 1β (IL-1β) and ionized calcium binding adapter molecule 1 (Iba1) of BV-2 cells were analyzed. Total 34 compounds with significant different volatilities were identified. α-hexylcinnamaldehyde, nerolidol, hexahydrofarnesyl acetone, dodecanal and decanal were predicted as the top 5 key compounds, SRC, EGFR, VEGFA, HSP90AA1 and ESR1 were the top 5 key targets, meanwhile the binding energies between them were less than -3.9 kcal/mol. BV-2 cells were activated by LPS with morphological changes, JGEOs not only could clearly reverse the changes, also significantly inhibited the production of NO and ROS, suppressed the expressions of TNF-α, IL-1β and Iba1. The findings indicate that JGEOs could inhibit the overactivation of microglia characterized by decreasing the neuroinflammatory and oxidative stress responses through the multi-compound and multi-target action modes, which support the traditional use of JGEOs in treating neuroinflammation-related disorders.